2003
DOI: 10.1016/j.bbrc.2003.10.054
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of p53 in α4β1 integrin-mediated resistance of B-CLL cells to fludarabine

Abstract: We recently showed that alpha4beta1 integrin induces B-cell chronic lymphocytic leukemia (B-CLL) cell resistance to fludarabine-induced apoptosis via upregulation of Bcl-xL. We have now studied whether p53 was involved in this response. Cells from five B-CLL patients with wild-type p53 determined by DNA sequencing, or from the EHEB cell line, cultured on the alpha4beta1 ligand H/89 during fludarabine treatment, showed significantly higher viability (P Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 29 publications
4
21
1
Order By: Relevance
“…Further work is ongoing to identify the factor(s) since maneuvers to reduce the activity or levels of the protective factor may augment the efficacy of some therapeutic approaches. Similar to other investigators [36,37], we have not seen the same kind of protection with MSE soluble factors for CLL B-cells exposed to fludarabine where physical contact between stroma and CLL B-cells appears to be necessary for protection to occur (data not shown). Therefore, the mechanisms by which MSE protect CLL B-cells from drug induced death appears to depend to a certain extent on the drugs mechanism of action.…”
Section: Discussionsupporting
confidence: 74%
“…Further work is ongoing to identify the factor(s) since maneuvers to reduce the activity or levels of the protective factor may augment the efficacy of some therapeutic approaches. Similar to other investigators [36,37], we have not seen the same kind of protection with MSE soluble factors for CLL B-cells exposed to fludarabine where physical contact between stroma and CLL B-cells appears to be necessary for protection to occur (data not shown). Therefore, the mechanisms by which MSE protect CLL B-cells from drug induced death appears to depend to a certain extent on the drugs mechanism of action.…”
Section: Discussionsupporting
confidence: 74%
“…It is well established that fludarabine induces p53 expression 22 and we have shown that interfering with this expression by crosslinking a4b1 integrin induces cell survival. 23 In results not shown, we did not observe induction of p53 in the present study, thus ruling out a role for this protein in the AT514 apoptotic pathway.…”
Section: Discussioncontrasting
confidence: 55%
“…4,6 Bone marrow stromal cells have been shown to protect normal and malignant hematopoietic cells from damaging events, including drug-induced cell death. [7][8][9][10][11][12] Normal hematopoiesis is regulated by the adhesive interaction of hematopoietic cells with the bone marrow microenvironment, as well as by growth factors and cytokines expressed by different types of bone marrow cells. 12 The bone marrow microenvironment consists of stromal cells and extracellular matrix proteins such as fibronectin, collagen and laminin.…”
Section: Introductionmentioning
confidence: 99%